2014
DOI: 10.1038/jes.2014.48
|View full text |Cite
|
Sign up to set email alerts
|

Estimating drinking-water ingestion and dermal contact with water in a French population of pregnant women: the EDDS cohort study

Abstract: The aim of the present study, a part of the Endocrine Disruptor Deux-Sèvres (EDDS) cohort study, was to estimate water-use habits of pregnant French women. The study population consisted of 132 pregnant women living in Deux-Sèvres (France) in 2012-2013, in areas where drinking water is exclusively produced by surface water. Drinking-water data included ingested water (tap, bottled and filtered) and ingestion place (home, work and elsewhere). Dermal contact with water included showering, bathing, swimming, spa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…A recent study we conducted in Deux-Sèvres on pregnant women (EDDS cohort study), showed that 94% of them drank home tap water and only 48+% drank bottled water) [38]. Moreover, as low income women may drink more bottled water than high income women, because they considered that their tap water quality is worse [39]; we have maybe overestimated atrazine metabolite exposure of women from most deprived areas.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study we conducted in Deux-Sèvres on pregnant women (EDDS cohort study), showed that 94% of them drank home tap water and only 48+% drank bottled water) [38]. Moreover, as low income women may drink more bottled water than high income women, because they considered that their tap water quality is worse [39]; we have maybe overestimated atrazine metabolite exposure of women from most deprived areas.…”
Section: Discussionmentioning
confidence: 98%
“…In the United States, it has been observed that pregnant and non-pregnant women do not differ in tap water consumption [49]. Furthermore, recent results from the Endocrine Disruptor Deux-Sèvres (EDDS) cohort study showed that 71% of pregnant women drank tap water [50] so it may not have affected our estimates. Besides, using ecological data on drinking-water prevents selection bias that can be found in cohort studies.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, selection bias is controlled by trained PMI nurses wishing to facilitate the enrolment of pregnant women facing di culties. Enrolment bias is thereby avoided, whereas preceding studies highlighted the fact that participants for this type of study are mostly women with a high socio-economic level [48]. However, in such a cohort, selection bias can still be expected [77] especially for pregnancy cohorts, insofar as women with a high socio-educational level are likely to feel more concerned [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the EDDS (Endocrine Disruptors Deux-Sèvres) cohort study, 83% of French women consumed canned food [48]. Thus, we calculated the number of participants based on the primary outcome measure (consumption measure) using a two-sided paired sample t-test with 0.05 level of signi cance two-way design and β = 0.20.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation